The Effect of Family Visit Management on Anxiety Levels Among Patients in the Intensive Care Unit: A Scoping Review - Ajeng Andini Sutisnu; Firman Sugiharto; Henny Yulianita; Theresia Eriyani (Jurnal Berita Ilmu Keperawatan, 2023)
Several studies identified the effect of family visits on reducing patient and family anxiety levels. However, until now there has been no review that synthesizes the results of these studies on this population. This review aimed to identify the effect of family visit management on the anxiety level of patients and families in the ICU. This Study used a scoping review method using CINAHL, PubMed, Science Direct and search engines Google Scholar. The keywords used in English were "family visitation OR visits" AND "anxiety disorders OR anxiety OR generalized anxiety disorder" AND "ICU OR intensive care unit OR critical care." The criteria for selecting the articles included full-text articles in English and published in 2013-2023. The study selection process used the PRISMA-ScR flow chart. We found 11 articles discussing the management of family visits to the anxiety of ICU patients. Based on the results of the analyzed studies, it shows that there are several types of scheduled visit management (in and out hours), flexible family visitations, limited visits, regular visits, and online methods. In general, participants in the studies analyzed showed reduced levels of anxiety, and most studies indicated that flexible visits were positively related to satisfaction with the services provided in the ICU. Furthermore, it is advised that the visiting policies in ICU be modified and that families be given the option to participate in patient care through scheduled attendance and involvement. Keywords: Anxiety, Critical illness, Intensive Care Unit, Visit Management